A study on operational issues faced by manufacturing firms implementing Traditional Kanban System (TKS) - Mohamad Firdaus, Mohd Yasin (2014)
Just-In-Time (JIT) manufacturing philosophy is a systems that were originally designed for deterministic production environments such as constant processing times and smooth and stable demand. However, once implemented, JIT is fraught with numerous types of uncertainties, including variations in processing time and demand, planned interruptions such as preventive maintenance and unplanned interruptions such as equipment failure. These uncertainties lead to lowered production throughput, decreased machine utilization, increased order completion time and greater backlogs and overtime requirements. This disquisition focus on the study of the operational issues existed in the tool employed as control mechanism in JIT, the Traditional Kanban System (TKS). After an extensive qualitative study using in-depth interview and literature reviews, the performance of TKS were analysed and the weakness and ﬂaw of the system were used as data of this research. The operational issues were then analysed and suggestion to address those issues were drawn out based on the variation (modiﬁcation) of Kanban system